Picosecond primary photoprocesses of bilirubin bound to human serum albumin. - Greene, B I (1981)
We measure the fluorescence quantum yield of bilirubin bound to its highest-affinity site on human serum albumin to increase from about 0.001 near room temperature to 0.5 at 77 K. The quantum yield for configurational (Z leads to E) photoisomerization about the meso double bonds concomitantly decreases from about 0.22 to less than 0.01 over the same temperature range in reciprocal relationship to the fluorescence yield. Transient absorption spectra recorded after excitation with a 0.5-ps pulse of 305-nm light decay with a lifetime of 19 +/- 3 ps at 22 degrees C and 35 +/- 7 ps at 2 degrees C. Bilirubin undergoes the same photoisomerization reaction in chloroform solution, in which a similar short-lived (17 +/- 3 ps at 22 degrees C) transient is observed. From these and other data we conclude that configurational isomerization of bilirubin is the predominant nonradiative pathway that competes with pigment fluorescence, that photoisomerization proceeds via a short-lived (much less than 18 ps) partially twisted excited-singlet-state intermediate, and that bilirubin remains relatively unihibited with respect to photoisomerization when bound to human serum albumin.